Communication Strategies Used by Teacher in Teaching Speaking Skill at MTs Al-Falah Jeneponto - Lestari, Putri Ayu; Dollah, Syarifuddin; Muhalim, Muhalim (Journal of Excellence in English Language Education, 2025)
This research aims to find out the communication strategies used by English teachers in teaching speaking skills and how the communication strategies used by English teachers in teaching speaking skills. The subjects of this research were two English teachers in MTs al-Falah Jeneponto. This research used descriptive qualitative method. The data sampling technique used was purposive sampling. The researcher used observation checklist and interview as instruments to collect data in this research. Based on the research findings, the results show that there are three communication strategies used by the two teachers which consist of achievement or compensatory strategies, stalling or time gaining and interactional strategies. Two teachers implemented it by: (1) achievement or compensatory strategies were used when explaining English material, usually mixing two languages, namely English and Indonesian, used by translating words one by one when students did not understand the sentences the teacher said, then used by the two teachers sign language such as when doing pantonyms, facial expressions and voice intonation apart from that it was used by reconstructing sentences without changing the meaning to be conveyed, and was used by describing or paraphrasing an object or target of action. (2) the strategy of stalling or time gaining, used by buying time when both teachers forget the words or sentences, they want to convey, and (3) interactional strategies, used by means of the ongoing learning process and finding expressions of lack of understanding trendy the form of words and forgetting how to pronounce them correctly, the teacher collaborates with students to find out the meaning or ask for help in understanding the word and pronounce it.